T-FINDER: a highly sensitive, pan-HLA platform for functional T cell receptor and ligand discovery - Cetin, Miray; Pinamonti, Veronica; Schmid, Theresa; Boschert, Tamara; Mellado Fuentes, Ana; Kromer, Kristina; Lerner, Taga; Zhang, Jing; Herzig, Yonatan; Ehlert, Christopher; Hernández, Miguel; Samaras, Georgios; et al. (Science advances, 2024)
Effective, unbiased, high-throughput methods to functionally identify both class II and class I HLA-presented T cell epitopes and their cognate T cell receptors (TCRs) are essential for and prerequisite to diagnostic and therapeutic applications, yet remain underdeveloped. Here, we present T-FINDER [T cell Functional Identification and (Neo)-antigen Discovery of Epitopes and Receptors], a system to rapidly deconvolute CD4 and CD8 TCRs and targets physiologically processed and presented by an individual’s unmanipulated, complete human leukocyte antigen (HLA) haplotype. Combining a highly sensitive TCR signaling reporter with an antigen processing system to overcome previously undescribed limitations to target expression, T-FINDER both robustly identifies unknown peptide:HLA ligands from antigen libraries and rapidly screens and functionally validates the specificity of large TCR libraries against known or predicted targets. To demonstrate its capabilities, we apply the platform to multiple TCR-based applications, including diffuse midline glioma, celiac disease, and rheumatoid arthritis, providing unique biological insights and showcasing T-FINDER’s potency and versatility.
Online veröffentlicht: 02. Februar 2024
Gesehen am 21.08.2024